Kajian Teologi ‘Penebusan’ dalam Kitab Rut dan Implikasinya Pada Masa Kini - Miranda Br Ginting (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
Redemption is God's saving work for mankind. Redemption in the Old Testament leads us to one book that tells of redemption, namely the book of Ruth. This study uses a qualitative research method with a literature study approach, namely, the Bible against various data sources and texts that support and have a correlation with this research. The author examines the theology of redemption in the book of Ruth and its implications for today. Redemption in the book of Ruth shows the story of